Where are natural gas prices heading, and what are the environmental consequences for Latin America? - Vásquez Cordano, Arturo (2018)
There was an upward trend in energy commodity prices since 2000, but with the surge in supply coming from unconventional oil and gas resources in North and South America, the trend in natural gas prices has become downward in recent years. However, the exploitation of these resources is generating public concerns due to the possible adverse environmental impacts of using hydraulic fracturing and other techniques on underground water. The purpose of this paper is to address the following questions: are there super cycles in natural gas prices? What are the environmental consequences in Latin America of the exploitation of unconventional gas given the cyclical behavior of gas prices and how can governments implement environmental policies to regulate unconventional gas extraction? Three super cycles in natural gas prices are identified with the last peak occurring in 2006. Our analysis indicates that the instable political situation and institutional weakness, the governmental intervention through asset nationalization and state-owned oil companies, the lack of transparent investment rules, high capital expenditures to develop LNG export projects and the exploration of shale resources, as well as the pre-salt discoveries in Brazil make uncertain that the shale gas boom achieve a large impact in Latin America during the current gas price super cycle.